(untitled) (Papeles, 2024)
The objective of this article is to reflect on the research teaching proposal constituted around the development of the subjects Thesis Design Seminar and Thesis Seminar in the Bachelor of Social Work – hereinafter LTS – of the Faculty of Legal and Social Sciences from the National University of the Litoral (FCJS-UNL). The text is constituted with the purpose of generating inputs that allow us to revisit our teaching practices and contribute to the construction of a critical view about the ways of teaching and learning the craft of social research in the public University. For its development, we recover our own ethnographic records based on our participation in different instances shared with students and teaching colleagues during the course in 2023 of the two subjects that make up the proposal: face-to-face classes in classroom spaces, virtual consultation meetings, emails and informal conversations with teachers and students in everyday university life. While those of us who carry out the research are subjects participating in the same processes that we study, the research is aligned with “ethnographies at home” and auto-ethnographies, in which our proximity has also become an object of reflection.